2001
DOI: 10.1136/jnnp.71.4.448
|View full text |Cite
|
Sign up to set email alerts
|

Brain temperature, body core temperature, and intracranial pressure in acute cerebral damage

Abstract: Objectives-To assess the frequency of hyperthermia in a population of acute neurosurgical patients; to assess the relation between brain temperature (ICT) and core temperature (Tc); to investigate the eVect of changes in brain temperature on intracranial pressure (ICP). Methods-The study involved 20 patients (10 severe head injury, eight subarachnoid haemorrhage, two neoplasms) with median Glasgow coma score (GCS) 6. ICP and ICT were monitored by an intraventricular catheter coupled with a thermistor. Internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
191
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 269 publications
(207 citation statements)
references
References 24 publications
(14 reference statements)
14
191
1
1
Order By: Relevance
“…8) Pyrexia is common in the acute stage of severe neurological disease and cerebral metabolism increases more than systemic metabolism due to the rise in temperature. 8) We previously observed that the difference between ventricular and rectal temperatures was greater in patients requiring continuous ventricular drainage for acute hydrocephalus due to SAH, intracerebral hematoma, or brain tumor, than in patients with chronic hydrocephalus due to various etiologies. 5) However, brain temperature might vary depending on the phase of the clinical course.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8) Pyrexia is common in the acute stage of severe neurological disease and cerebral metabolism increases more than systemic metabolism due to the rise in temperature. 8) We previously observed that the difference between ventricular and rectal temperatures was greater in patients requiring continuous ventricular drainage for acute hydrocephalus due to SAH, intracerebral hematoma, or brain tumor, than in patients with chronic hydrocephalus due to various etiologies. 5) However, brain temperature might vary depending on the phase of the clinical course.…”
Section: Discussionmentioning
confidence: 99%
“…The temperature of the brain depends on three major factors: local heat production, cerebral blood flow, and the temperature of the perfusing blood. 8) T. Omori et al…”
Section: Discussionmentioning
confidence: 99%
“…In the severely brain-injured population, jugular vein temperature more accurately represents core body temperature instead of brain temperature. The difference becomes greater if the patient is febrile [26,27]. In a study by Rumana et al, the difference between jugular bulb and intraparenchymal brain temperature did not correlate with a decrease in global cerebral flow, injury severity, or type of injury [25].…”
Section: Monitoring Brain Temperaturementioning
confidence: 94%
“…In fact, a two-to four-degree difference may exist [25][26][27]. In the severely brain-injured population, jugular vein temperature more accurately represents core body temperature instead of brain temperature.…”
Section: Monitoring Brain Temperaturementioning
confidence: 99%
See 1 more Smart Citation